Ambidextrous leadership, innovativeness and sustainable performance of micro-finance firms in Kenya - Bor, Beatrice Jepkemboi; Kimwolo, Andrew; Githaiga, Peter Nderitu (Journal of Asian Business Strategy, 2025)
This paper empirically examines the influence of ambidextrous leadership on the sustainable performance of microfinance institutions in Kenya and the mediating role of innovativeness. The study adopted an explanatory research design incorporating cross-sectional and correlational methodologies. Data was collected from a sample of 215 branch managers from both deposit-taking and credit-only institutions in Kenya through structured questionnaires. Validity and reliability were ensured using expert review, factor analysis, and Cronbach’s alpha. The hypotheses were tested using Hayes model 4, with firm size and age as control variables. The results revealed that ambidextrous leadership had a positive and statistically significant direct effect on sustainable performance. Moreover, innovativeness significantly mediated this relationship, indicating that ambidextrous leaders enhance sustainability partly by fostering innovation. While firm age positively influenced performance, firm size had no significant effect. These findings demonstrate that leadership that balances exploration and exploitation contributes to long-term sustainability, particularly when it enhances organizational innovativeness. This study advances empirical understanding in microfinance contexts and offers actionable insights for managers and policymakers. MFI leaders should invest in innovation-driven practices to strengthen performance outcomes, while regulatory agencies and industry associations should support capacity-building and innovation ecosystems that enable adaptive leadership and long-term institutional sustainability.